Students' Learning Motivation Analysis in Contextual Learning on Faraidh Fiqh Material - Kahfi, Askhabul; Yansyah, Dandi; Farida, Ida (Universitas Islam Negeri Raden Intan Lampung, 2022)
This research aims to assess students’ motivation in contextual learning on Faraidh material. The research subjects were the twelfth-grade students of SMK Kumala Lestari Cianjur. This research is a descriptive analysis. The motivational aspects of attention, self-confidence, satisfaction, and relevance were used to construct motivational instruments, which consisted of twenty-six statement items. The statement items had been validated. The reliability test showed that the dependability criterion was very high. The percentages for each aspect of motivation showed high motivation criteria. So it can be concluded lest implied that contextual learning motivated students to learn faraidh material. Therefore, teachers are essential in creating a positive and conducive learning environment during the contextual learning process.